Copolymer SJ-1 as a Fluid Loss Additive for Drilling Fluid with High Content of Salt and Calcium. (18th August 2014) - Quan, Hongping; Li, Huan; Huang, Zhiyu; Zhang, Tailiang; Dai, Shanshan
Abstract : A ternary copolymer of 2-acrylamide-2-methyl propane sulfonic acid (AMPS), acrylamide (AM), and allyl alcohol polyoxyethylene ether (APEG) with a side chain polyoxyethylene ether ( C 2 H 4 O ) n SJ-1 were designed and synthesized in this work. Good temperature resistance and salt tolerance of "– SO 3 - " of AMPS, strong absorption ability of "amino-group" of AM, and good hydrability of side chain polyoxyethylene ether ( C 2 H 4 O ) n of APEG provide SJ-1 excellent properties as a fluid loss additive. The chemical structure of ternary copolymer was characterized by Fourier transform infrared (FTIR) spectroscopy. The molecular weight and its distribution were determined by gel permeation chromatography (GPC). The API fluid loss of drilling fluid decreased gradually with the increasing concentration of NaCl and CaCl2 in the mud system. SJ-1 was applied well in the drilling fluid even at a high temperature of 220°C. Results of zeta potential of modified drilling fluid showed the dispersion stability of drilling fluid system. Scanning electron microscopy (SEM) analysis showed the microstructure of the surface of the filter cake obtained from the drilling fluid modified by SJ-1.